2018
DOI: 10.1111/omi.12209
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the competition between Streptococcus sanguinis and Streptococcus mutans in the dental biofilm

Abstract: During dental caries, the dental biofilm modifies the composition of the hundreds of involved bacterial species. Changing environmental conditions influence competition. A pertinent model to exemplify the complex interplay of the microorganisms in the human dental biofilm is the competition between Streptococcus sanguinis and Streptococcus mutans. It has been reported that children and adults harbor greater numbers of S. sanguinis in the oral cavity, associated with caries-free teeth. Conversely, S. mutans is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Our results of the mixed streptococcal biofilm agree with previous studies on the mixed growth of these two species: the competition between S. mutans and S. sanguinis has been documented, with S. sanguinis being associated with oral health (Belda-Ferre et al, 2012) and causing a delay in the colonisation of S. mutans (Caufield et al, 2000) by repressing its growth through H2O2 production (Kreth et al, 2005;Valdebenito et al, 2018), thereby reducing dental caries (Zhu et al, 2018). The H2O2 produced by S. sanguinis would also explain the slower growth of S. mutans in the presence of the S. sanguinis supernatant, which was observed when the toxicity testing between these organisms was conducted.…”
Section: Discussionsupporting
confidence: 91%
“…Our results of the mixed streptococcal biofilm agree with previous studies on the mixed growth of these two species: the competition between S. mutans and S. sanguinis has been documented, with S. sanguinis being associated with oral health (Belda-Ferre et al, 2012) and causing a delay in the colonisation of S. mutans (Caufield et al, 2000) by repressing its growth through H2O2 production (Kreth et al, 2005;Valdebenito et al, 2018), thereby reducing dental caries (Zhu et al, 2018). The H2O2 produced by S. sanguinis would also explain the slower growth of S. mutans in the presence of the S. sanguinis supernatant, which was observed when the toxicity testing between these organisms was conducted.…”
Section: Discussionsupporting
confidence: 91%
“…S. sanguinis and S. mutans compete for the same ecological niche and have similar metabolic characters 35 . S. sanguinis can produce hydrogen peroxide and sanguicin to inhibit the growth of S. mutans , moreover, it can also inhibit S. mutans bacteriocins synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…When S. sanguinis and S. mutans were inoculated onto half-strength BHI plates, the previously inoculated species could inhibit the growth of the later inoculated species, but simultaneous inoculation by both species resulted in coexistence [ 95 ]. Furthermore, the authors showed that H 2 O 2 produced by S. sanguinis repressed the growth of S. mutans [ 95 ], a conclusion that has also been supported by clinical research and in silico analysis [ 96 , 97 ]. Conversely, mutacins I and IV secreted by S. mutans suppressed the survival of S. sanguinis ( Figure 2 A) [ 95 ].…”
Section: The Relationship Of S Sanguinis With Denmentioning
confidence: 94%
“…However, deletion of the gene encoding the superoxide dismutase SodA did not affect H 2 O 2 resistance in S. sanguinis , while the same mutation decreased H 2 O 2 resistance in S. gordonii [ 106 ]. In addition, a glutathione peroxidase BasA was predicted to be a gene responsible for the degradation of H 2 O 2 in S. sanguinis [ 97 ].…”
Section: The Relationship Of S Sanguinis With Denmentioning
confidence: 99%